Outbreak of Velogenic Viscerotropic Newcastle Disease in Broilers - Musa, I.W.; Abdu, P.A.; Sackey, A.K.B.; Oladele, S.B.; Lawal, S.; Yakubu, I.U. (International Journal of Poultry Science, 2010)
This report describes an outbreak of an acute, highly lethal, Newcastle Disease (ND) in two broiler flocks that were intensively managed and vaccinated against Newcastle disease. The broiler flocks (325) were four weeks and (450) were six weeks old at the time of the outbreak. Clinical characteristics of the disease included a 100% morbidity, increasing high mortality i.e. 40 birds (day one), 70 birds (day two), 180 (day three) and the entire flocks consisting of 755 birds were lost by the fifth day. Clinical features observed included severe depression, gasping, anorexia, cyanosis and subcutaneous haemorrhages of the legs and shank. Gross lesions seen were severe congestion of skeletal muscles and visceral organs and severe haemorrhages and congestion of the proventriculus, cecal tonsils and trachea, air saculitis with severely congested and pneumonic lungs were observed as well. Ten cloacal swabs from dead and sick birds were tested using a Rapid Newcastle Disease and Avian Influenza Antigen Detection Test Kits. This Chromatographic- immunoassay tested positive for ND and negative for AI confirming the presence of ND viral antigen. Four dead and live birds taken to National Veterinary Research Institute (NVRI) Vom, Nigeria for further confirmation were tested using rapid test kit, haemagglutination inhibition test and viral isolation. These tests were also negative for AI but positive for vvND. Clinical signs and gross lesions of ND and Highly Pathogenic Avian Influenza (HPAI) seem not to be distinguishable in the field. This is likely going to affect disease reporting and actions to be taken. Vaccination against ND should not be totally relied upon especially when birds are not seromonitored pre and post vaccination.